Legal Reformulation of Land Cultivation Rights Area Limits: Synchronizing Distributive Justice and Public Welfare - Nikko Meyndo Arissa Putra Pratama; Iwan Permadi; Hamidi Masykur (IBLAM LAW REVIEW, 2026)
This research analyzes the urgency of reformulating maximum area limits for Land Cultivation Rights (HGU) for legal entities within the framework of Welfare State theory. As of 2026, inequality in land tenure in the plantation sector remains a crucial issue due to corporate land accumulation through corporate groups, which exceeds the bounds of social fairness and marginalizes local farmers. This study uses a normative-juridical method with statutory and conceptual approaches. It examines agrarian legal instruments, including the role of the Land Bank and the implementation of Government Regulation Number 48 of 2025 concerning the Management of Abandoned Areas and Land. The findings show that current HGU area limit regulations remain formal-administrative and fail to address the substantive aspect of beneficial ownership. As a result, disguised monopolistic practices continue to hinder equitable redistribution of natural resources. This study proposes a reformulation model based on three pillars: accumulative area limits across affiliated legal entities, mandatory integration of 30% plasma land as an absolute requirement for rights renewal, and optimization of land downsizing for agrarian reform. The study concludes that HGU limitation must function as an instrument to correct agrarian inequality and realize sustainable social welfare in Indonesia.